PENGARUH PEMANASAN GLOBAL TERHADAP PERUBAHAN IKLIM - Dahlia Sarkawi (Universitas Bina Sarana Informatika, 2011)
Global warming is a matter for us all, not just the story that came from distant lands about exhaust fumes huge factories, ice melts, polar bears are almost extinct, or menggurun agricultural land in Africa. Food, choice of vehicle, home to the waste that we discard carelessly, took an important role in climate change on Earth. We played a major role in heating the earth, but we can also become part of the solution. If global warming continues unchecked, many of the land will sink. Some of them are the islands in our country, perhaps also including the island that we live in today. The polar ice caps will disappear in the next 30 years; of course it's not just destroy the polar bears, but also would raise sea levels. Keywords: Global Warming, Climate Change.